1987
DOI: 10.1007/bf00187244
|View full text |Cite
|
Sign up to set email alerts
|

Mescaline: excitatory effects on acoustic startle are blocked by serotonin2 antagonists

Abstract: The ability of serotonin2 (5-HT2) antagonists to block the excitatory effects of mescaline on the acoustic startle reflex were analyzed. Mescaline (20 mg/kg) caused a consistent increase in the amplitude of the acoustic startle reflex. This effect was blocked in a dose-related fashion by the 5-HT2 antagonist ritanserin (ED50 dose = 0.25 mg/kg IP). In contrast, even a high dose of ritanserin (2.0 mg/kg) did not block the excitatory effects of amphetamine on startle. Other 5-HT2 antagonists (ketanserin, cinanser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 57 publications
(50 reference statements)
0
7
1
Order By: Relevance
“…Unlike others who have reported an increase in startle reaction (Davis 1987;Geyer et al 1978), we observed a decrease in startle produced by mescaline 100 mg/kg at 60 min post-treatment. This could reflect the robust motor changes produced by the drug.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Unlike others who have reported an increase in startle reaction (Davis 1987;Geyer et al 1978), we observed a decrease in startle produced by mescaline 100 mg/kg at 60 min post-treatment. This could reflect the robust motor changes produced by the drug.…”
Section: Discussioncontrasting
confidence: 85%
“…On the other hand, a 0-to 20-min pretest interval after either i.p. or s.c. administration was used by others in various tests, e.g., Wing et al (1990); Sykes (1986); Harris et al (1978); Gorelick and Bridger (1977); Davis (1987); Geyer et al (1979); Silva and Calil (1975). Interestingly, in previously published drug discrimination studies, animals were able to discriminate mescaline 5 and 15 min after relatively low doses of mescaline (9.9 and 15 mg/kg; Browne et al 1974;Hirschhorn and Winter 1971).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Importantly, acute administration of LSD to rats reduced habituation of tactile startle provoked by air-puffs (Figure 2) (Geyer et al, 1978; Geyer and Braff, 1987), an effect that is lost when LSD is administered chronically (Braff and Geyer, 1980). Mescaline also attenuates habituation of acoustic startle in rats (Davis, 1987), and this effect is blocked by the 5-HT 2A/2C antagonists ritanserin, ketanserin, LY 53857, and cinanserin. Psilocybin, however, did not have significant effects on startle reactivity or habituation when tested in human subjects (Gouzoulis-Mayfrank et al, 1998c; Vollenweider et al, 2007; Quednow et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Because the 5-HT2 receptor also mediates hallucinations, 5-HT2 receptor agonists are not suitable for inferences about the role of 5-HT2 receptors in anxiety models [34], Among the antagonists, there are useful tools to study the role of 5-HT2 receptors. There quency or the monophasic square-wave pulses was adjusted after each trial (1 trial/min) to titrate to the effective frequency for escape.…”
Section: -Ht2 Receptormentioning
confidence: 99%